2021
DOI: 10.1136/rapm-2020-102388
|View full text |Cite
|
Sign up to set email alerts
|

Simple screening model for identifying the risk of sleep apnea in patients on opioids for chronic pain

Abstract: BackgroundThere is an increased risk of sleep apnea in patients using opioids for chronic pain. We hypothesized that a simple model comprizing of: (1) STOP-Bang questionnaire and resting daytime oxyhemoglobin saturation (SpO2); and (2) overnight oximetry will identify those at risk of moderate-to-severe sleep apnea in patients with chronic pain.MethodAdults on opioids for chronic pain were recruited from pain clinics. Participants completed the STOP-Bang questionnaire, resting daytime SpO2, and in-laboratory p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Seven fair-quality studies (n = 2589) assessing clinical prediction tools or screening questionnaires compared with facility-based polysomnography were included, 4 of which were new to this review (Table 1). Two evaluated the Berlin Questionnaire, 4 evaluated the STOP-BANG (snoring, tiredness, observed apnea, high blood pressure, BMI, age, neck circumference, gender) questionnaire, and 2 evaluated the Multivariable Apnea Prediction (MVAP) score—alone and when followed by an unattended home sleep test …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven fair-quality studies (n = 2589) assessing clinical prediction tools or screening questionnaires compared with facility-based polysomnography were included, 4 of which were new to this review (Table 1). Two evaluated the Berlin Questionnaire, 4 evaluated the STOP-BANG (snoring, tiredness, observed apnea, high blood pressure, BMI, age, neck circumference, gender) questionnaire, and 2 evaluated the Multivariable Apnea Prediction (MVAP) score—alone and when followed by an unattended home sleep test …”
Section: Resultsmentioning
confidence: 99%
“…The STOP-BANG questionnaire includes 8 dichotomous items (snoring, tiredness, observed apnea, blood pressure, BMI, age, neck circumference, and gender) . The 4 studies assessing the accuracy of the STOP-BANG questionnaire enrolled diverse populations and used different scoring criteria and additional variables to determine a positive screen result . Detailed characteristics of each study are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Simple screening model for identifying the risk of sleep apnea in patients on opioids for chronic pain: an infographic Rajnish K Gupta , 1 Eric S Schwenk 2…”
Section: Infographicmentioning
confidence: 99%
“…Selvanathan et al propose an additional step to the screening model by adding a home oxygen desaturation test. 1 With this additional tool, the authors were able to rule out OSA for nearly 38% more patients than by just doing the STOP-Bang Questionnaire or resting oxygen saturation alone. The addition of home oximetry to detect oxygen desaturation events is a simple and effective way to screen for OSA in this high-risk population while reducing the number of patients without OSA who needed to undergo a sleep study.…”
Section: Introductionmentioning
confidence: 99%